Effects of a chronotype-adapted diet on weight loss, cardiometabolic health, and gut microbiota: study protocol for a randomized controlled trial - Dinu, Monica; Lotti, Sofia; Pagliai, Giuditta; Napoletano, Antonia; Asensi, Marta Tristan; Giangrandi, Ilaria; Marcucci, Rossella; Amedei, Amedeo; Colombini, Barbara; Sofi, Francesco (Current controlled trials in cardiovascular medicine, 2024)
Background Obesity and its associated health complications have become a global public health concern, necessitating innovative approaches to weight management. One emerging area of research focuses on the influence of chronotype, an individual’s preferred timing for daily activities, on eating habits, weight regulation, and metabolic health. Recent observational studies suggest that the misalignment between an individual’s chronotype and external cues, such as meal timing, may contribute to metabolic dysregulation and obesity, but evidence from intervention studies is still limited. This study protocol describes a randomized controlled trial designed to explore the effects of a chronotype-adapted diet, compared with a diet with a conventional calorie distribution, on weight loss, cardiometabolic health, and gut microbiota composition. Methods A total of 150 overweight/obese adults will be recruited for this 4-month parallel-group, randomized, two-arm, open-label, superiority trial with 1:1 allocation ratio. Participants will be randomly assigned to either the intervention group or the control group. The intervention group will receive a low-calorie chronotype-adapted diet with a calorie distribution adapted to the individual chronotype (morning or evening), optimizing meal timing according to their peak metabolic periods. The control group will follow a standardized low-calorie healthy eating plan without considering chronotype. Both diets will have equivalent daily calorie content, adjusted according to gender and starting weight. Anthropometric measurements, body composition, blood, and fecal samples will be obtained from each participant at the beginning and the end of the study. The primary outcome is weight change from baseline. Secondary outcomes are changes from baseline in body mass index (BMI), fat mass, lipid and glycemic profile, fecal microbiota profile, and short-chain fatty acids (SCFAs). Discussion The results of this randomized controlled trial have the potential to advance our understanding of the complex interactions between chronotype, diet, body weight, and health outcomes. By providing evidence for personalized dietary interventions based on individuals’ circadian preferences, this research could offer insights into personalized nutrition strategies. Such knowledge could guide the development of innovative dietary interventions to optimize the prevention and management of overweight and obesity, while also improving the risk profile of these individuals. Trial registration ClinicalTrials.gov NCT05941871. Registered on 18 May 2023.